Countermeasures Against Online Soccer Gambling Crimes By Surabaya Police - Anggara Pratama Naibaho, Dawan; Muriman Setyabudi, Chairul; Nita, Surya (Pelopor Publikasi Akademika, 2025)
Gambling poses a significant threat to societal norms and can impede national progress on both material and spiritual fronts. Consequently, a rational approach is imperative in addressing this issue, which includes robust law enforcement policies and the prosecution of offenders. This research delves into the Surabaya City Police's efforts to combat online soccer gambling and seeks to analyze the modus operandi of suspects involved in such activities, as well as the challenges and obstacles encountered by the Cyber Unit III of the Surabaya City Police Criminal Investigation Unit. Employing a qualitative descriptive exploratory methodology, this study utilizes primary and secondary data gathered through observation, interviews, and document analysis. The findings of this research are anticipated to serve as a valuable resource for understanding the complexities of combating online gambling and to inform strategies for enhancing police effectiveness in responding to public reports of this illicit activity.